Inter‐individual variation in weaning among rhesus macaques (Macaca mulatta): Serum stable isotope indicators of suckling duration and lactation. Issue 10 (18th August 2015) - Reitsema, Laurie J.; Partrick, Katherine A.; Muir, Andrew B.
Abstract : Weaning is a transition in early development with major implications for infant survival and well‐being, and for maternal lifetime reproductive success. The particular strategy a primate mother adopts in rearing her offspring represents a negotiation between her ability to invest and her need to invest, and can be considered adaptive and influenced by biological and social factors. Any investigation into how and why maternal weaning strategies differ among non‐human primates is limited by the precision of the measurement tool used to assess infants' weaning ages. Stable carbon and nitrogen isotope analysis of soft tissues (e.g., hair, nails, feces, urine, blood) offers an objective means of monitoring the weaning status of infants. In this study, we assess stable isotope ratios in blood serum from 14 captive rhesus macaque dyads ( Macaca mulatta ) at infant ages 2, 5, 6, 7, 8, and 10 months to estimate the timing of weaning events. Male infants wean earlier than female infants. Infants with the lowest birth weights wean latest. Most infants wean upon reaching 2.5 times their birth weights, sooner than when weaning elsewhere has been predicted for captive cercopithecine primates. The longest weaning periods (ca. 10 months) are observed among infants of small mothers. The shortest weaning period, between 2 and 5 months, was among the lowest ranking dyad. Parity and mothers' ages had no discernible effect on the timing of weaning events. The stable carbon and nitrogen isotope values of dams during lactation are significantly different than those of a non‐lactating adult female outgroup, raising questions about the suitability and selection of adult comparative baselines in studies where lactating mothers cannot be sampled longitudinally (e.g., bioarchaeology; paleontology). Am. J. Primatol. 78:1113–1134, 2016. © 2015 Wiley Periodicals, Inc.